The Influence of Visiting Lecturer Communicator Credibility Modeling on Indonesian-Malaysian Students' Learning Motivation - Neni Yulianita; Kiki Zakiah; Tresna Wiwitan (Jurnal Edusci, 2025)
Background. The success of a Visiting Lecturer program depends not only on material quality but also on communicator credibility, which is crucial for fostering strong student motivation to participate in international forums and succeed in the educational process. Objectives. The short-term research objective is to assess the effectiveness of the Visiting Lecturer program, while the long-term objective is to support policy development for the collaborative program between the two universities. Methods. The study used a comparative quantitative method to explain differences between the two subject groups. Results. The study found a significant positive effect of communicator credibility in the Visiting Lecturer program on Indonesian–Malaysian student motivation, with teaching quality influencing Indonesian students’ motivation by 61.4% and Malaysian students’ motivation by 47.6%. Conclusion: The credibility of communicators in the Visiting Lecturer Collaboration Program plays an essential role in strengthening the motivation of Indonesian–Malaysian students, highlighting its importance in enhancing the effectiveness of international academic collaboration. Implementation. The findings can be implemented by strengthening communicator credibility through lecturer preparation, communication training, and collaborative teaching strategies to further enhance student motivation in international academic programs.